Principal's technology leadership and technological integration in Kedah National secondary schools: Professional development as a moderator - Thannimalai, Raamani; Raman, Arumugam (2017)
Purpose - Principals as technology leaders and teachers as facilitators must have the skills and knowledge to implement the 21st Century Education (Roblyer & Doering, 2015).A principal’s responsibility is becoming even more challenging as schools have to produce skilled and creative workforce to meet the demands of the Industrial Revolution 4.0 and the Digital Economy.Therefore, principals should possess ICT skills and knowledge to guide and motivate teachers to integrate technology in the classroom in line with the seventh shift of the Malaysia Education Blueprint (2013-2025) (Ministry Of Education, 2013) and the National Transformation 2050.In the past three decades, most studies related to technology use in secondary schools (Fullan, 2001; Senge, 1990; Michael, 1983; Johnson and Cooley, 2001; Hamzah, Juraime, Hamid, Nordin & Attan, 2014) agree that principal’s leadership plays a major role in the technology integration in the classroom. In addition, studies such as Richardson and McLeod (2011) and Wang (2010), suggest that the professional development of principals should be further investigated.The aim of this study is to identify the relationship between the five constructs of the National Education Technology Standards-Administrator (2009) namely Visionary Leadership, Digital Age Learning Culture, Excellence in Professional Practice, Systemic Improvement and Digital Citizenship with technology integration (ISTE, 2009).In addition, professional development is investigated as a moderator based on previous researcher’s recommendations.Methodology - In this cross sectional survey, systematic random sampling will be carried out to select 79 principals and 370 teachers from national secondary schools in Kedah.. The Principals Technology Leadership Survey (PTLA) which is based on NETS-A (2009) and Survey of Technology Experiences’ will be administered to principals while the Learning with ICT: Measuring ICT Use in the Curriculum Instrument will be administered to the teachers from the same school.The instruments were also verified as valid by two experts in the field. Descriptive statistics analysis will be carried out using the SPSS version 23 while the Inferential Statistics Analysis will be carried out using Partial Least Squares Structural Equation Modeling (Smart PLS-SEM).As this is a proposal paper, a pilot test was administered to 13 principals and 213 teachers of 13 secondary schools in Perlis to verify that both the instruments are reliable.Findings - The Cronbach alpha obtained from the pilot test show that all constructs obtained the value higher then 0.7 (Nunnally, 1978) except for Visionary Leadership. Item-item correlation was analyzed and one item was deleted to obtain a better Cronbach alpha coefficient.